Functional substrates for flexible organic photovoltaic cells - Niggemann, M; Ruf, D; Bläsi, B; Glatthaar, M; Riede, M; Müller, C; Zimmermann, B; Gombert, A (Society of Photo-Optical Instrumentation Engineers, 2005)
Along with efficiency and lifetime, costs are one of the most important aspects for the commercialization of organic solar cells. Thinking of large scale production of organic solar cells by an efficient reel-to-reel process, the materials are expected to determine the costs of the final product. Our approach is to develop functional substrates for organic solar cells which have the potential for cost effective production. The functionality is obtained by combining periodically microstructured substrates with lamellar electrode structures. Such structured substrates were fabricated by cost effective replication from masterstructures that were generated by large area interference lithography. Two cell architectures were investigated - holographic microprisms and interdigital buried nanoelectrodes. A structure period of 20μm in combination with a 2μm wide metal grid was chosen for the microprism cells based on the results of electrical calculations. Current-voltage curves with reasonable fill factors were measured for these devices. A significant light trapping effect was predicted from optical simulations. Interdigital buried nanoelectrodes are embedded in the photoactive layer of the solar cell. Separated interdigital metal electrodes with a sufficiently high parallel resistance were manufactured despite a small electrode distance below 400 nm. Experimental results on first photovoltaic devices will be presented. We observe an insufficient rectification of the photovoltaic device which we attribute to partial electron injection into the gold anode.